2016
DOI: 10.2147/ijn.s108939
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of tendon–bone healing via the combination of biodegradable collagen-loaded nanofibrous membranes and a three-dimensional printed bone-anchoring bolt

Abstract: A composite biodegradable polymeric model was developed to enhance tendon graft healing. This model included a biodegradable polylactide (PLA) bolt as the bone anchor and a poly(D,L-lactide- co -glycolide) (PLGA) nanofibrous membrane embedded with collagen as a biomimic patch to promote tendon–bone interface integration. Degradation rate and compressive strength of the PLA bolt were measured after immersion in a buffer solution for 3 months. In vitro biochemical characteristics and the n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 38 publications
0
24
0
Order By: Relevance
“…However, in the current study the PLA scaffolds have undergone a glass transition process during 3D printing, which made it more solid than pure PLA fibers and probably decreased its degradability to some extent. In comparison with previous studies on the degradability of the PLA in vivo, it is obvious that this polymer is not degraded in a short period (35). Due to the requirement of prolonged mechanical integrity for osteogenic regeneration, the study did not accept this issue as a disadvantage.…”
Section: Discussionmentioning
confidence: 73%
“…However, in the current study the PLA scaffolds have undergone a glass transition process during 3D printing, which made it more solid than pure PLA fibers and probably decreased its degradability to some extent. In comparison with previous studies on the degradability of the PLA in vivo, it is obvious that this polymer is not degraded in a short period (35). Due to the requirement of prolonged mechanical integrity for osteogenic regeneration, the study did not accept this issue as a disadvantage.…”
Section: Discussionmentioning
confidence: 73%
“…Kang et al [47] developed electrospun membranes based on biodegradable polylactic acid and hydrosoluble collagen for tissue engineering applications and the MTT assay used to evaluate the survival rate of L929 cells cultivated in the presence of the membranes indicated that they were suitable for the cell proliferation. In another study, poly(d,l-lactide-co-glycolide) (PLGA) nanofibrous membranes embedded with collagen were also found to be stable and biocompatible, which made them suitable to promote tendon-bone interface integration [4]. Some in vitro studies have shown that silver nanoparticles can induce toxicity at different cell levels and can cause various health problems [46,48,49], but used in appropriate concentrations they can be good candidates for many applications in the medical field, mainly due to their antimicrobial and anti-inflammatory properties [50].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, large animal models of ACL reconstruction have been used to evaluate graft-bone healing. Previous studies have shown that hydrophilic biomaterials promote bone healing and osseointegration 17,[28][29][30][31][32] . Lang et al 28 reported that, in a human bone defect model, the chemically modified moderately rough, hydrophilic (i.e., SLActive) implant surface performed better than moderately rough, hydrophobic (i.e., SLA) implant surface in the rate and degree of osseointegration during the early phase of healing (i.e., 2 and 4 wk).…”
Section: Discussionmentioning
confidence: 99%